Kedudukan Hadits Maudhu Dalam Ajaran Islam - Lubis, Wildan Salsabila; Suparta, M.; Bakar, Romlah Abu (Madani: Jurnal Ilmiah Multidisiplin, 2025)
According to the scholars of hadith, hadith maudhu is a hadith that in the sanad or eyes proved to contain falsehood because there is a falsification by a narrator or there is a strong indicator that the hadith does not come from the Prophet. Even some scholars state that false hadith is the worst hadith and can not be used as argument in any case, including in the context of fadha'il a'mal (priority of charity), unless its falsity is explicitly explained so as not to mislead the people. as well as the contemporary era. Scholars have worked hard ever since to identify and eradicate false hadiths, by developing a methodology of in-depth and systematic criticism. In today’s digital age, the challenges in the spread of false hadith are ever greater, yet it also opens up opportunities for wider tackling through technology. This study demonstrates that the success of maudhu’ hadith criticism depends on the continuity of the scholarly tradition, the adaptation of classical methods, and the improvement of hadith literacy in society. Thus, the current and future generations of Muslims can still maintain the authenticity and integrity of Prophet Muhammad’s teachings scientifically and responsibly.